CHINESE CULTURAL VALUES AS A PART OF "BELT AND ROAD INITIATIVE" PROJECT - Xie, Fei; Kalashnyk, Nataliia; Fan, Zhenxuan; Mkrtichan, Oksana; Hryhorenko, Valeriia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The Belt and Road Initiative (BRI) is a global development strategy adopted by the Chinese government in 2013. Some experts believe that this project is an attempt to spread Chinese dominance in the region and adjacent territories through the economical initiative. But together with the economic purposes, the BRI aims spreading the Chinese cultural and citizenship values over the local cultures of the countries involved by forming a common cultural space. This article aims to show how the Chinese government uses the BRI Project to demonstrate the achievements of Chinese society in social and cultural life, introduce the modern China to the world, level stereotypes about the Chinese worldview and lifestyle, which were formed in the world due to a certain isolation of China, lack of reliable information about China in the world and some other reasons. At the article the following methods, typical for theoretical research, were used: observation, analysis, synthesis, analogy, comparing, narration, conclusion making etc. The result of the research is the summation of implicit information and the confirmation of the hypothesis that this project is of great cultural importance (to familiarize the world with modern China and its socio-cultural achievements more than in the opposite direction) and uses a wide range of tools to achieve goals.